Investigating the role of extracellular polymeric substances produced by Parachlorella kessleri in Zn(II) bioremediation using atomic force microscopy - Passucci, Victoria (2024)
Microalgae, such as Parachlorella kessleri, have significant potential for environmental remediation, especially in removing heavy metals like zinc from water. This study investigates how P. kessleri, isolated from a polluted river in Argentina, can remediate zinc. Using atomic force microscopy (AFM), the research examined the interactions between Zn particles and cells grown with different nitrogen sources—nitrate or ammonium. The results showed that cells grown with nitrate produced extracellular polymeric substances (EPS), while those grown with ammonium did not. Raman spectroscopy revealed distinct metabolic responses based on the nitrogen source, with nitrate-grown cells showing altered profiles after zinc exposure. Zinc exposure also changed the surface roughness and nanomechanical properties of the cells, particularly in those producing EPS. AFM force spectroscopy experiments then confirmed strong Zn binding to EPS in nitrate-grown cells, while interactions were weaker in ammonium-grown cells that lacked EPS. Overall, our results elucidate the critical role of EPS in Zn removal by P. kessleri cells and show that Zn remediation by P. kessleri is mediated by EPS adsorption. This study underscores the significance of regulating nitrogen sources to stimulate EPS production, offering insights that are essential for subsequent bioremediation applications.